Recent northward range extension of Nerita yoldii (Gastropoda: Neritidae) on artificial rocky shores in China. (4th September 2018) - Wang, Jie; Yan, Hai-Yang; Cheng, Zhi-Yuan; Huang, Xiong-Wei; Wang, Wei; Ding, Meng-Wen; Dong, Yun-Wei
Abstract: Extensive coastal infrastructures built along the Chinese coastline have effectively created a new marine 'Great Wall' that has had a significant effect on the biogeography of intertidal species in the region by creating new habitat for colonization. Recent colonization by Nerita yoldii of the artificial rocky shores in the Yangtze River Delta has contributed to a northward shift of this species' range. Here, we study the range expansion and phylogeographic pattern of this species. Our four-year field survey showed a northward range expansion of N. yoldii on the artificial rocky shores. A phylogeographic analysis of populations from both artificial and natural rocky shores showed lower genetic diversity and fewer private haplotypes in newly colonized artificial shore populations. All the populations were clustered into three groups, one consisting of the three southernmost natural rocky-shore populations, a second that included all but one of the artificial-substrate populations and the two northernmost natural rocky-shore populations, and a third that included the offshore artificial-island population. These results indicate that N. yoldii has rapidly expanded its northern distribution limit and that the coastal artificial structures, together with increasing SST in the Yangtze River Delta, have played a crucial role in this range expansion.